COMPUTER MODULE FOR ANIMATING THE MOVEMENT OF THE CONNECTING ROD GROUP OF THE KDAM PROGRAM WHEN DETERMINING KINEMATIC AND DYNAMIC PARAMETERS - SHCHERBAN, VOLODYMYR; MELNIK, GENADIJ; GOLDBERG, MARJANA; KIRICHENKO, ANTON; SHCHERBAN, YURYJ (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The development of new schemes of the thread feeding system requires an operational assessment of the value of the tension in front of the working zone. The objective function in the tasks of optimizing technological processes is the minimum necessary tension. The development of special computer programs for determining the tension in the working area makes it possible to determine the necessary technological parameters. The variable parameter in the objective function is the sum of the angles of coverage of the working bodies by the thread. The use of a computer program allows you to determine the tension and change in relative tension in the filling zones of technological machines, which allows you to optimize the shape of the thread supply line even at the stage of designing the technological process. A computer module was developed for the animation of the movement of the connecting rod-slider group, which is a component of the KDAM program for determining the kinematic and dynamic parameters of the connecting rod-slider group of the mechanisms of textile and light industry machines, which allows at the preliminary design stage to visually evaluate the behavior of individual links of the connecting rod mechanism of the slider group and determine the coordinates, projections of velocities and accelerations of the center of mass of the connecting rod, the slider and the points of attachment of the links of the Asura groups on the connecting rod.The KDAM program is a structural element of a computer software complex for assessing the intensity of technological processes in the light and textile industry when determining the change in the relative tension of the thread in the filling zones on the technological equipment. Kinematic and dynamic analysis of flat mechanisms plays a significant role in the design of new mechanisms and modernization of existing ones. The results obtained during these studies can be used to calculate the strength of individual links, their inertial characteristics, optimization of structural parameters of mechanisms, and minimization of consumed energy. The computer module of the KDAM program for determining the kinematic and dynamic parameters of the connecting rod-slider group of mechanisms of light industry machines allows you to determine the coordinates, projections of velocities and accelerations of the center of mass of the connecting rod, slider and the point of attachment of the links of the Asura groups on the connecting rod. During the dynamic analysis of the operation of the connecting rod-slider group, the projections of the full reaction in the joints between the crank and the connecting rod, between the connecting rod and the slider, and between the slider and the fixed guide are determined.
Keywords: computer module; motion animation; visualization; kinematic parameters; connecting rod and slider group